A 3D Nanoporous Ni–Mo Electrocatalyst with Negligible Overpotential for Alkaline Hydrogen Evolution. Issue 7 (8th July 2014) - Wang, Yuhang; Zhang, Guoxin; Xu, Wenwen; Wan, Pengbo; Lu, Zhiyi; Li, Yaping; Sun, Xiaoming
Abstract The front cover artwork is provided by the group of Prof. Xiaoming Sun and Prof. Pengbo Wan at Beijing University of Chemical Technology (PR China). The image shows a Ni–Mo electrocatalyst for the hydrogen evolution reaction (HER). It is revealed that the performance of the fabricated 3D Ni–Mo electrocatalyst with negligible overpotential, high current density, ultrahigh activity, and durable stability for alkaline HER, challenges that of Pt catalysts. Read the full text of the article at 10.1002/celc.201402089.